2013
DOI: 10.1073/pnas.1303491110
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling potentiates nevogenesis

Abstract: Cellular senescence is a stable proliferation arrest associated with an altered secretory pathway (senescence-associated secretory phenotype). Cellular senescence is also a tumor suppressor mechanism, to which both proliferation arrest and senescence-associated secretory phenotype are thought to contribute. The melanocytes within benign human nevi are a paradigm for tumor-suppressive senescent cells in a premalignant neoplasm. Here a comparison of proliferating and senescent melanocytes and melanoma cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
76
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 54 publications
11
76
0
2
Order By: Relevance
“…We built cell line specific models using RNA-Seq data (Bürckstümmer et al, 2013; Di Ruscio et al, 2013; Pawlikowski et al, 2013; Zhang et al, 2015) to specify active genes in each cell line. Active genes are identified by many algorithms based on a quantitative threshold of expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We built cell line specific models using RNA-Seq data (Bürckstümmer et al, 2013; Di Ruscio et al, 2013; Pawlikowski et al, 2013; Zhang et al, 2015) to specify active genes in each cell line. Active genes are identified by many algorithms based on a quantitative threshold of expression.…”
Section: Resultsmentioning
confidence: 99%
“…The mRNA-sequencing datasets (Bürckstümmer et al, 2013; Di Ruscio et al, 2013; Pawlikowski et al, 2013; Zhang et al, 2015) were downloaded, and Trimmomatic (Bolger et al, 2014) was used to trim low quality reads. The reads were aligned to the GRCh38 reference human genome using STAR (Dobin et al, 2013) (4 STAR parameters were set: ‘–outSAMstrandField intronMotif’, ‘–outFilterType BySJout’, ‘–outFilterIntronMotifs RemoveNoncanonicalUnannotated’, ‘–outSAMtype BAM SortedByCoordinate’, others are set as default), and then quantified using Cufflinks with all parameters set as defaults (Trapnell et al, 2011), using the unit of fragments per kilobase of exon per million fragments (FPKM) for all genes.…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2C). Additionally, publicly accessible RNA-Seq data of independently derived melanocyte specimens (NCBI GEO GSE46805 and GSE33092) all show truncated ESRP1 expression in melanocytes (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have demonstrated that melanocytes expressing senescence markers accumulate in human skin, and this was significantly associated with increased facial wrinkles, higher perceived age and age‐associated elastin morphology in the papillary dermis (Waaijer et al , , ). Interestingly, expression of p16 INK4A , a known marker of senescence, was shown to co‐localise almost exclusively to melanocytes in the epidermis, suggesting that melanocytes represent the major p16 INK4A senescent cell population in the epidermis of human skin (Waaijer et al , , ; Pawlikowski et al , ). This observation is surprising given that fully differentiated melanocytes have an extremely low replicative capacity (Jimbow et al , ; Taylor et al , ).…”
Section: Introductionmentioning
confidence: 99%